Pelatihan Inovasi Olahan Singkong Kekinian untuk Pemberdayaan Ekonomi Perempuan PKK Bumijo Kulon Kota Yogyakarta - Riyadh, Luthfi Riyadh Rahman; Restiana, Reza; Suparmanto, Nova (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Community empowerment through the utilization of local food potential is an essential strategy to support economic independence, particularly for underprivileged women groups. This Community Service Program aimed to enhance the skills of PKK Bumijo Kulon members in processing cassava (Manihot esculenta Crantz) into contemporary food products with higher economic value while equipping participants with business management and digital marketing skills. Method: The implementation method applied a participatory approach through preparation, training, hands-on practice, mentoring, and evaluation stages. The program was conducted over two days, with digital marketing training on the first day and cassava processing practice on the second day, producing innovative products such as cassava cheese sticks, cassava with milk, chocolate cassava chips, and cassava “lumpur surga.” Results: The results indicated improvements in participants’ knowledge and skills in product innovation and the use of social media for promotion. Evaluation using questionnaires showed an average score of 3.5–3.8 (out of 4), reflecting a high satisfaction level. Conclusion: This program effectively improved technical skills, entrepreneurial motivation, and contributed significantly to strengthening the local economy.